Effectiveness and safety of acupuncture for postoperative ileus following gastrointestinal surgery: A systematic review and meta-analysis - Ye, Zi; Wei, Xuqiang; Feng, Shouquan; Gu, Qunhao; Li, Jing; Kuai, Le; Luo, Yue; Xi, Ziqi; Wang, Ke; Zhou, Jia (PLOS ONE, 2022)
Background Postoperative ileus (POI) is an important complication of gastrointestinal (GI) surgery. Acupuncture has been increasingly used in treating POI. This study aimed to assess the effectiveness and safety of acupuncture for POI following GI surgery. Methods Seven databases (PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure, Wan fang Data, VIP Database for Chinese Technical Periodicals, and Chinese Biomedical Literature Database) and related resources were searched from inception to May 30, 2021. Randomized controlled trials (RCTs) reporting the acupuncture for POI in GI were included. The quality of RCTs was assessed by the Cochrane Collaboration Risk of Bias tool, and the certainty of the evidence was evaluated by the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. A meta-analysis was performed by using RevMan 5.4 software. Results Eighteen RCTs involving 1413 participants were included. The meta-analysis showed that acupuncture could reduce the time to first flatus (TFF) (standardized mean difference [SMD] = −1.14, 95% confidence interval [CI]: −1.54 to −0.73, P < 0.00001), time to first defecation (TFD) (SMD = −1.31, 95% CI: −1.88 to −0.74, P < 0.00001), time to bowel sounds recovery (TBSR) (SMD = −1.57, 95% CI: −2.14 to −1.01, P < 0.00001), and length of hospital stay (LOS) (mean difference [MD] = −1.68, 95% CI: −2.55 to −0.80, P = 0.0002) compared with usual care. A subgroup analysis found that acupuncture at distal acupoints once daily after surgery had superior effects on reducing TFF and TFD. A sensitivity analysis supported the validity of the finding. Acupuncture also manifested an effect of reducing TFF, TFD and TBSR compared with sham acupuncture but the result was not stable. Relatively few trials have reported whether adverse events have occurred. Conclusions Acupuncture showed a certain effect in reducing POI following GI surgery with very low-to-moderate quality of evidence. The overall safety of acupuncture should be further validated. More high-quality, large-scale, and multicenter original trials are needed in the future.